The zookeeper's wife [videorecording (DVD)] - Chastain, Jessica, 1977-; Heldenbergh, Johan, 1967-; Brühl, Daniel, 1978-; Ackerman, Diane, 1948- (Universal Pictures Home Entertainment, 2017)
The real-life story of one working wife and mother who became a hero to hundreds during World War II. In 1939 Poland, Antonina Zabinska and her husband, Dr. Jan Zabinski, have the Warsaw Zoo flourishing under his stewardship and her care. When the Germans invade their country, they are forced to report to the Reich's newly appointed chief zoologist, Lutz Heck. To fight back on their own terms, Antonina and Jan covertly begin working with the Resistance.